Smart Kulkas dengan Fitur SMS untuk Melaporkan Ketersediaan Bahan Makanan - I Wayan Degeng; Michael Santoso (Universitas Indraprasta PGRI Jakarta, 2018)
Refrigerator is one of household appliances used daily to keep foodstuffs fresh. To find out whether the contents of the refrigerator are running low or run out, a user must check it directly by opening the door and viewing the contents. It will be troublesome to know the contents of the refrigerator when the user is outdoors because he or she must first call someone at home. One of solutions offered is by modifying the refrigerator so that the user can check the contents of the refrigerator by sending a short message (SMS) via mobile phone and the refrigerator can also send notification via SMS to the user if the contents of the refrigerator are running out. Equipment added to the refrigerator is a microcontroller in Arduino Uno R3 equipped with load sensors, and infrared sensors as food detectors and with GSM module for sending and receiving short messages. The study is conducted to design a modified refrigerator and to test the modification result. The result is a smart refrigerator system that can send SMS if the food supply in the refrigerator is running out.